INTEGRATED PROGRAMS (IP) PADA ROGRAM KEMITRAAN MASYARAKAT (PKM) DI UKM BUNDA SUKOLILO BARU, KECAMATAN BULAK, SURABAYA - Theresia Widihartanti; Aniek Sulestiani; Titiek Indira Agustin; Nirmalasari Idha Wijaya; Urip Prayogi (Jurnal Layanan Masyarakat (Journal of Public Services), 2020)
Sukolilo Baru is one of the tourist destination centers focused on selling dried and semi-finished fish products so that it is much sought after by tourists. However, the arrangement of processing rooms is far from adequate standards. Integrated Programs (IP) in the community service include (a) Tutorial on the cultivation of eggplant and sea cucumbers; (b) Tutorial on GMP; (c) Making crackers drying tools as appropriate technology. Drying crackers made from seafood still relies on sunlight and still uses space on the edges of the road. One of the tools needed is a weatherproof, eggplant and sea cucumber drying tool. This has become the foundation of the Faculty of Engineering and Marine Sciences of UHT to implement knowledge in its engineering field to make an effective drying tool by utilizing the limited land, which is above the storeroom of dried eggplant and sea cucumbers. By using the glass drying device, the drying time will be 3 days from 7-10 days, so that the effectiveness of the drying tool has been proven; (d) Arrangement of PIRT as the legality of the product for consumption. Thus, the Integrated Programs (IP) implemented by the FTIK community service team succeeded in improving the welfare of Sukolilo Baru, Surabaya.abstrakKelurahan Sukolilo Baru merupakan salah satu pusat tujuan wisata fokus pada penjualan produk ikan  kering dan setengah jadi sehingga banyak diminati oleh wisatawan. Namun, penataan ruang pengolahan jauh dari standar memadai. Integrated Programs (IP) pada pengabdian kepada masyarakat tersebut meliputi (a) Tutorial tentang budidaya terung dan teripang; (b) Tutorial tentang GMP; (c) Pembuatan alat penjemur kerupuk sebagai teknologi tepat guna. Penjemuran bahan kerupuk berbahan baku hasil laut masih mengandalkan sinar matahari dan masih memakai ruang di pinggir-pinggir jalan. Salah satu alat yang dibutuhkan adalah alat penjemuran terung dan teripang basah yang tahan cuaca. Hal inilah yang menjadi landasan Fakultas Teknik dan Ilmu Kelautan UHT untuk mengimplementasikan pengetahuan dalam bidang tekniknya untuk membuat alat penjemur yang tepat guna dengan memanfaatkan lahan yang terbatas, yaitu di atas gudang penyimpanan terung dan teripang kering. Dengan menggunakan alat penjemur kaca tersebut, lama penjemuran menjadi 3 hari dari sebelumnya 7-10 hari, sehingga efektifitas alat penjemur tersebut telah terbukti; (d) Pengurusan PIRT sebagai legalitas produk untuk dikonsumsi. Dengan demikian, Integrated Programs (IP) yang dilaksanakan oleh tim Penmas FTIK berhasil dalam meningkatkan kesejahteraan warga Kelurahan Sukolilo Baru, Surabaya.